2021
DOI: 10.3390/geosciences11010031
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Mineralogical Characterization of Construction Materials from Historical Buildings of Ferrara (Italy)

Abstract: This paper presents a chemical-mineralogical characterization of construction materials from medieval Renaissance buildings of Ferrara (NE Italy) to provide an insight into the nature and provenance of the raw materials used. Biagio Rossetti was an Italian architect and urbanist from the city of Ferrara. From 1483, he was the architect of the Duke of Ferrara Ercole I d’Este who in 1492 assigned him the project of enlarging the city of Ferrara. Biagio Rossetti is still famous because he designed and built many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The optical stereomicroscope (90× total magnification) equipped with MOTICAM 2500 5.0 M pixel webcam using the Motic Images Plus 2.0 ML software was used for reflected light observation on all the samples to define their structural aspect (grain size and texture), clasts dimensional, and morphological aspect of their state of conservation [35]. In this specific work, OTLPM provided information about the quality of the work to produce the mortar [36,37].…”
Section: Stratigraphic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical stereomicroscope (90× total magnification) equipped with MOTICAM 2500 5.0 M pixel webcam using the Motic Images Plus 2.0 ML software was used for reflected light observation on all the samples to define their structural aspect (grain size and texture), clasts dimensional, and morphological aspect of their state of conservation [35]. In this specific work, OTLPM provided information about the quality of the work to produce the mortar [36,37].…”
Section: Stratigraphic Analysesmentioning
confidence: 99%
“…The iso-distribution of conductivity highlighted an anomalous area in correspondence with the gap in the plaster (colored in red in Figure 5 to be compared with Figure 4), which indicated that the finishing layers created a barrier to humidity (colored in green in Figure 5). 2500 5.0 M pixel webcam using the Motic Images Plus 2.0 ML software was used fo flected light observation on all the samples to define their structural aspect (grain size texture), clasts dimensional, and morphological aspect of their state of conservation In this specific work, OTLPM provided information about the quality of the work to duce the mortar [36,37].…”
Section: Surface Conductivitymentioning
confidence: 99%
“…The powders were prepared by pressing the tablets on boric acid support for XRF analysis. The chemical characterization of the collected samples was determined by X-Ray Fluorescence (XRF) analysis, carried out at the Department of Physics and Earth Sciences, University of Ferrara, with a wavelength dispersion spectrometer ARL Advant-XP (Thermo Fisher Scientific, Waltham, MA, USA) [29]. This technique allowed the determination of the major elements, expressed as a percentage by oxide weight (SiO 2 , TiO 2 , Al 2 O 3 , Fe 2 O 3 , MnO, MgO, CaO, Na 2 O, K 2 O, P 2 O 5 ), and of the following trace elements reported in ppm (parts per million): Ba, Ce, Co, Cr, La, Nb, Ni, Pb, Rb, Sr, Th, V, Y, Zn, Zr, Cu, Ga, Nd, S, Sc.…”
Section: Chemical and Mineralogical Characterizationmentioning
confidence: 99%
“…Two test sites in the city of Ferrara were considered in this work: in the city center, called "urban location" (44 • The city of Ferrara is characterized by a historic center, rich in ancient buildings and historic churches [45,55,56]. The walls and facades of this buildings and monuments become dirty due to the presence of metal particles and/or oxides that create black crusts on the surfaces of the buildings [45].…”
Section: Study Area Sampling and Meteorological Conditionsmentioning
confidence: 99%
“…Accordingly, the ability of atmospheric particulate matter to transport foreign substances could be the cause of the deterioration of the monuments and of the cultural heritage sites [40][41][42]. The walls and facades of important buildings and historical monuments become dirty due to the presence of metal particles and/or oxides that could create black crusts on the surfaces of the buildings [43][44][45], which require human intervention to be removed.…”
Section: Introductionmentioning
confidence: 99%